Development of Microbiology Module “Antibacterial Effect of Ginger Rhizome Extract to Inhibit the Growth of Propionibacterium acnes Bacteria” as a Teaching Material to Improve Students’ Problem Solving Skill - Mahesti, Tika; Hastuti, Utami Sri; Sari, Murni Sapta (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This research is a research and development of module on the topic